Efficacy of Tripterygium glycosides in immune-mediated kidney diseases as a immunomodulation drug in combination with conventional immunosuppressive agents: a systematic review and meta-analysis of randomized controlled trials - Li, Yaotan; Hou, Jinyi; Wu, Xiaochang; Liu, Chang; Zhou, Mengqi; Lin, Shijia; Liu, Weijing; Wang, Yaoxian; Zheng, Huijuan (Frontiers in Pharmacology, 2025)
BackgroundImmune-mediated kidney diseases involve the immune system attacking the kidneys, resulting in damage and dysfunction. Tripterygium glycosides (TG) are known for their strong immunosuppressive and anti-inflammatory effects and are commonly used alongside traditional immunosuppressive agents. However, evidence-based support for the combined use of these treatments in immune-mediated kidney diseases remains insufficient and requires further validation.PurposeThe aim of this study is to evaluate the efficacy and safety of TG combined with immunosuppressive agents in the treatment of immune-mediated kidney diseases.Study designSystematic Review and Meta-Analysis of Randomized Controlled Trials (RCTs).MethodsWe searched nine electronic databases for articles from 1 January 2014 to 1 June 2025. We included the RCTs comparing TG combined with immunosuppressive agents versus immunosuppressive agents alone. Meta-analysis was performed according to the Cochrane Handbook.ResultsThirty-six RCTs were included, involving 3,455 patients with various conditions such as membranous nephropathy (MN), IgA nephropathy (IgAN), primary nephrotic syndrome (PNS) and others. The combined use of TG and immunosuppressive agents differs from the use of immunosuppressive agents alone in terms of clinical efficacy (RR = 1.26; 95%CI: 1.22–1.30), improvement in serum creatinine (Cr) (SMD = −0.86; 95%CI: −1.11 to −0.61), blood urea nitrogen (BUN) (SMD = −0.68; 95%CI: −1.05 to −0.31), 24-h urinary total protein (24h-UTP) (SMD = −0.93; 95%CI: −1.13 to −0.74), and serum albumin (ALB) (SMD = 1.30; 95%CI: 1.08–1.52). However, there is no statistically significant difference in the improvement of total cholesterol (TC) (SMD = −0.62; 95%CI: −1.39 to 0.16). In terms of overall safety, the combination therapy shows a statistically significant difference compared to the use of immunosuppressive agents alone (RR = 0.72; 95%CI: 0.58–0.90), but no differences were observed in gastrointestinal issues, liver damage, leukopenia, and infections. Additionally, our analysis found that the combination therapy has a significant advantage over the use of immunosuppressive agents alone in reducing the recurrence rate (RR = 0.21; 95%CI: 0.10–0.44). In terms of mechanisms, the final results indicate that there are differences in interleukin-6 (IL-6) and C-reactive protein (CRP) levels between the two groups, while no differences were observed in interleukin-1 (IL-1) and tumor necrosis factor (TNF-α). However, treatment course, TG dosage, and sample size are important factors influencing the results.ConclusionOur study suggests that the combination of TG with immunosuppressive agents offers more pronounced efficacy in treating immune mediated kidney diseases, without increasing the incidence of adverse reactions. However, our findings may be limited by the quality of the existing studies. High-quality RCTs are needed to provide more accurate evidence.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023473530.